Pharmacy-based alcohol-misuse services: current perspectives - Hattingh, H.; Tait, Robert (2017)
Context: Globally, the use of alcohol is a leading cause of mortality and morbidity. Opportunistic screening and brief interventions (SBIs) have been shown to be effective in reducing alcohol consumption in certain primary care settings and provide a means of reaching some of those who do not seek treatment for alcohol-related problems. Further, community pharmacies have the potential to reach consumers at an early stage of their alcohol use and incorporate intervention and advice into their role in providing medications. Aim: The purpose of this review was to inform pharmacists and stakeholders of the evidence base for SBI in community pharmacy settings. To date, there has been limited research on the effectiveness of alcohol SBI in community pharmacies, with a systemic review only identifying two randomized trials. Methods: This narrative review reports on the period 2007-2017, covering feasibility studies, pilot programs, and surveys of consumers and pharmacy staff attitudes relating to alcohol SBI in this setting. Studies were identified via MEDLINE, CINAHL, Google Scholar, and reference lists of relevant publications. Findings: The findings indicated that the provision of community pharmacy alcohol SBI requires training in communication and intervention skills and in some cases increasing confidence and alcohol-related knowledge. Consumers were generally receptive to the SBI approach but requested private areas for delivery of such. Conclusion: The high prevalence of "at risk" alcohol use in many countries and the low level of treatment seeking by this group means that novel approaches to engage opportunistically with these people is imperative in reducing alcohol-related harms. However, before committing routine health funding, these novel approaches need rigorous evaluation.